2021
DOI: 10.1136/bmjopen-2020-043194
|View full text |Cite
|
Sign up to set email alerts
|

Study into the reversal of septic shock with landiolol (beta blockade): STRESS-L Study protocol for a randomised trial

Abstract: IntroductionIn 2013, a single-centre study reported the safe use of esmolol in patients with septic shock and tachycardia who required vasopressor therapy for more than 24 hours. Although not powered to detect a change in mortality, marked improvements were seen in survival (adjusted HR, 0.39; 95% CI, 0.26 to 0.59; p<0.001). Beta blockers are one of the most studied groups of drugs but their effect in septic shock is poorly understood; proposed mechanisms include not only the modulation of cardiac function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The methods for this study were published. 12 The trial was conducted in full conformance with the principles of the Declaration of Helsinki 13 and to International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH)-Good Clinical Practice guidelines. The study procedures can be found in the study protocol (Supplement 1).…”
Section: Methodsmentioning
confidence: 99%
“…The methods for this study were published. 12 The trial was conducted in full conformance with the principles of the Declaration of Helsinki 13 and to International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH)-Good Clinical Practice guidelines. The study procedures can be found in the study protocol (Supplement 1).…”
Section: Methodsmentioning
confidence: 99%
“…Tachycardia and tachyarrhythmias in septic shock can worsen LV systolic and diastolic dysfunctions, and some studies have evaluated the use of short-acting beta-blockers, such as esmolol [107] , [108] or landiolol [109] , [110] to treat tachyarrhythmias with the goal of improving the prognoses of patients with septic shock. [111] , [112] However, few of these studies specifically evaluated SCM.…”
Section: Managementmentioning
confidence: 99%
“… 15 Therefore, cardio-selective beta-blockers may be a logic treatment option to control heart rate in these patients, without affecting inotropy and blood pressure, a concept currently tested in clinical trials. 16 Importantly, Morelli et al . 17 have demonstrated that beta-blocker treatment is feasible and safe in patients with septic shock in sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%